Rewritings of memory and disconcert in the stories of Valeria Correa Fiz and Vera Giaconi (Anclajes, 2026)
This article analyses the different representations of traumatic memory, especially historical memory, in the books of short stories La condición animal (2016) and Hubo un jardín (2022), by Valeria Correa Fiz, and Carne viva (2011) and Seres queridos (2017), by Vera Giaconi, two authors from the Southern Cone of the secondpost-dictatorship generation. Both coincide in their aim to disconcert the reader through a writing traversed by silences that increase the uncertainty and the shocking effect of the story. To achieve this, the writers make use of resources typical of non-mimeticnarratives, that is, the grotesque, the fantastic and, especially, the unusual. Consequently,this study aims to identify and unravel their mechanisms of distortion, as well as the expressive and ideological tensions with which they problematise individual and collective memory.
Keywords: Valeria Correa Fiz; Vera Giaconi; Argentina; Literary Analysis; Collective Memory